KAJIAN SINTAKSIS SURAT KABAR NASIONAL: BERITA KEKALAHAN TIMNAS INDONESIA - Yesika Maya Ocktarani (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2014)
This paper provides information about the lexical system in articles of two national newspapers in providing information about the loss of Indonesian national football team in AFF Cup 2010. Every newspaper has its own style in providing information, thus through this paper the different way of writing can be seen from the words which are used in the articles. From two national newspapers, the data is taken and analyzed using descriptive quantitative method based on word and sentences classification. From the analysis, the structure of sentences is used as reminder that every language has specific symbol and forms. The result shows that newspaper A is more comprehensive in providing information than B. Newspaper A has more complex sentences and various words compare with the other one. From the words can also be seen that B only focus on how supporters suffered by the loss, instead of explaining the information about the loss itself.Kata Kunci : sintaksis, pilihan kata, media cetak